The Urgency of Abandoning Negative Content on Social Media: A Hadith Review on Benefits and Priorities - Andika, Rosita; Anwar, Latifah (Universitas Ibn Khaldun, 2025)
This study aims to explore how the teachings of the hadith of the Prophet Muhammad SAW can be applied in the wise use of social media. In the modern context where social media has become an integral part of everyday life, it is important to understand how individuals can avoid useless content and replace it with constructive information. This study uses a qualitative approach through library data, where data is collected from various literature sources, including hadith humanities, scientific articles, and relevant online sources. The results of the study indicate that the teachings of the hadith about abandoning things that are not useful are very relevant in facing today's digital challenges. In this journal, the author also discusses practical strategies for abandoning useless content and replacing it with more constructive information. By understanding and applying the principles of the hadith in the use of social media, it is hoped that readers can find ways to make their experiences on social media more meaningful and productive. The results of this study are expected to contribute to the development of digital literacy among Muslims and increase awareness of moral responsibility in using social media.